(untitled) (Journal of Hama University, 2025)
The network of urban spaces in the city with its nodal components (squares, intersections, green spaces...) and interconnected components (streets, pedestrian paths, waterways...) and movement processes between them (transportation and movement), is considered one of the most important urban tools through which cities provide various services to their residents and visitors and enhance their social, economic and cultural performance. With the acceleration of urbanization and the increase in challenges at both the global and local levels, sustainability appears to be the most important goal that urban planning seeks to achieve. The group of urban spaces in the city achieves the best sustainable performance when it has the urban characteristics that qualify it to host dense, diverse, time-extended and available human activity for all. Therefore, the research seeks to identify the most important features of the vital urban spaces network and their urban characteristics at the functional and spatial levels in the city. The research provides a brief theoretical presentation of the developed acknowledgment of the role of urban spaces as an integrated performance network, followed by an analysis of several studies from different cities around the world that share analyzing the role of the network of urban spaces and how to evaluate and improve its performance. The research concludes with a set of features that distinguish the sustainable urban spaces network in the city, through which the performance of this network can be evaluated and improved continuously.